Reator controlado a tiristores: modelagem para análises sob condições de operação em regimes permanente e transitório - Fandi, Marcelo (1998)
This work deals with the modelling of the thyristor controlled reactor (TCR) static compensator, in the time domain. Firstly, the TCR basic theory is introduced. The TCR modelling and Computer implementation in the SABER simulator is then presented and discussed. Finally, the modelling performance is discussed through digital Computer simulations. The corresponding results found are then compared to measurement oscillograms. Besides, the great flexibility of the SABER simulator is also illustrated along the work.